Germline Pathogenic Variant Prevalence Among Latin American and US Hispanic Individuals Undergoing Testing for Hereditary Breast and Ovarian Cancer: A Cross-Sectional Study - Ossa Gomez, Carlos Andrés (2022)
PURPOSE: To report on pathogenic germline variants detected among individuals undergoing genetic testing for hereditary breast and/or ovarian cancer (HBOC) from Latin America and compare them with self-reported Hispanic individuals from the United States. METHODS: In this cross-sectional study, unrelated individuals with a personal/family history suggestive of HBOC who received clinician-ordered germline multigene sequencing were grouped according to the location of the ordering physician: group A, Mexico, Central America, and the Caribbean; group B, South America; and group C, United States with individuals who self-reported Hispanic ethnicity. Relatives who underwent cascade testing were analyzed separately. RESULTS: Among 24,075 unrelated probands across all regions, most were female (94.9%) and reported a personal history suggestive of HBOC (range, 65.0%-80.6%); the mean age at testing was 49.1 ± 13.1 years. The average number of genes analyzed per patient was highest in group A (A 63 ± 28, B 56 ± 29, and C 40 ± 28). Between 9.1% and 18.7% of patients had pathogenic germline variants in HBOC genes (highest yield in group A), with the majority associated with high HBOC risk. Compared with US Hispanics individuals the overall yield was significantly higher in both Latin American regions (A v C P = 1.64×10-9, B v C P < 2.2×10-16). Rates of variants of uncertain significance were similar across all three regions (33.7%-42.6%). Cascade testing uptake was low in all regions (A 6.6%, B 4.5%, and C 1.9%). CONCLUSION: This study highlights the importance of multigene panel testing in Latin American individuals with newly diagnosed or history of HBOC, who can benefit from medical management changes including targeted therapies, eligibility to clinical trials, risk-reducing surgeries, surveillance and prevention of secondary malignancy, and genetic counseling and subsequent cascade testing of at-risk relatives.